PENGARUH PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP NET PROFIT MARGIN (NPM) PADA PT.TIGA PILAR SEJAHTERA FOOD,TBK. - Sumiati; Aliah Pratiwi (Universitas Mahendradatta, 2023)
This study aims to examine the effect of Accounts Receivable Turnover and InventoryTurnover on Net Profit Margin (NPM) at PT Tiga Pilar Sejahtea Food, Tbk. Thepopulation in this study was 18 years old based on the purposive sampling method, asample of 10 years was obtained, namely in 2011-2020. In this study, the data wasprocessed using SPSS version 2020 with data analysis techniques consisting of; (1)Classical Assumption Test, namely Normality Test, Multicollinearity Test,Heteroscedasticity Test, Autocorrelation Test; (2) Multiple Linear Analysis; (3)Correlation and Determination Coefficients; (4) Partial test; and (5) Simultaneous test ofhypothesis testing method using a significant level of 5%. The results of the study showthat the Accounts Receivable Turnover variable has no partial significant effect on theNet Profit Margin (NPM), the Inventory Turnover variable has a partially significanteffect on the Net Profit Margin (NPM) and the influence of Receivable Turnover and Inventory Turnover has a simultaneous significant effect on the Net Profit Margin (NPM).) at PT Tiga Pilar Sejahtera Food, Tbk